ANALISIS DAMPAK KEPEMIMPINAN PADA UPAYA PENINGKATAN KINERJA GURU SMK X DI KOTA PEKANBARU - AQSA, MUHAMMAD ALI; SYABILLA, WIWIN (Eko dan Bisnis: Riau Economic and Business Review, 2022)
: This research was conducted at SMK X in Pekanbaru. This study aims to determine the effect of principal's leadership on teacher performance at SMK X in Pekanbaru. The population in this study were all 36 teachers. The sampling technique in this study used the census method. The data analysis used in this study used quantitative methods. Based on the results of data processing carried out from the results of hypothesis testing with the t test, the t-count value (8.755) is greater than the t-table value (2.032), with a significant level of 0.000 <0.05, it can be concluded that Ho is rejected, which means leadership has a significant effect on teacher performance at SMK X in Pekanbaru. For the coefficient of determination (R2) the value of the coefficient of determination (R2) of 0.693 means that the contribution or contribution of the independent variable to the dependent variable is 0.693 or 69.3% while the remaining 30.7% is influenced by other variables that are ignored or not examined in this study